Pembelajaran Fiqih Di Kelas VII di MTs Negeri 2 Lahat: Menggali Best Practices Dan Strategi Mengajar: Learning Fiqh in Class VII at MTs Negeri 2 Lahat: Exploring Best Practices and Teaching Strategies - Dewi, Metta (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This research focuses on Fiqh learning in grade VII at MTs Negeri 2 Lahat with the aim of identifying best practices and effective teaching strategies. Through the analysis of various sources and relevant literature, this study analyzes the learning approaches that are successfully implemented as well as highlighting the importance of innovative and interactive methods in teaching Fiqh. The main findings of this study indicate that the incorporation of traditional methods with modern technology as well as student-centered approaches can add value in the teaching of Fiqh, making the material more relevant and easily understood by students. Approaches such as interactive discussions, the use of digital media, and simulations of religious practices are proven to increase students' engagement in learning, improving their understanding of Fiqh and its application in daily life. This study provides educators with insights into the importance of adapting teaching methods that are relevant to students' needs and learning styles, and explains how these best practices can be applied to produce effective and inspiring learning processes. This study is expected to be a source of reference for teachers in improving the quality of Fiqh learning through the application of innovative and empathic teaching strategies.